Mapping the Development of Egyptian Tafsir - Najah, Nailun (LP2M IAI Al-Khairat Pamekasan, 2023)
This article discusses the mapping of the development of interpretation in Egypt. This article discusses the development of interpretation in Egypt in the classical, middle and renewal phases. Where each phase has its own characteristics and methods. The classical Egyptian interpretation was greatly influenced by the Meccan madrasah, so that many of the interpretations circulating at that time were sourced from the narrations of Ibn Abbas. The second phase is the codification phase. This phase experienced quite significant development compared to the previous one. This period has more diverse methods and patterns of interpretation compared to the previous period. Interpretation in this period has begun to use the bi al-ra'y (dira>yah) approach. Next is the renewal phase. In this phase, the study of interpretation has begun a new chapter with the presence of the mujaddids of interpretation pioneered by 'Abduh and his student Rashīd Ridā with a new approach that is more objective and positions the Qur'an as a source of guidance as well as a problem solver for social problems that plague Muslims. This approach is what Adams calls